Efeito gastroprotetor de uma fração proteica isolada do látex de Plumeria rubra L. (APOCYNACEAE) em lesão gástrica induzida por etanol: envolvimento de receptores TRPV1, da via NO/GMPc/KATP e da glutationa - Pinheiro, Rachel Sindeaux Paiva (2012)
The Plumeria rubra is a laticifer plant of family Apocynaceae, popularly known as “Jasmim”. It is widely distributed in tropical and subtropical regions, including Brazil. This plant is commonly used for the treatment of syphilis, fever, and as a purgative. Some studies show that the latex of P. rubra has antioxidant and vasodilator activity. The aim of this study was to evaluate the gastroprotective effect of laticifers proteins of Plumeria rubra (PrLP) in ethanol-induced gastric damage, to investigate the possible involvement of TRPV1 receptors, NOcGMPKATP pathway and glutathione, and possible toxic effects. Animal handling and experimental protocols were registered on the Institutional Ethics Committee under number 057/2010. Swiss mice (n=8), fasting for 16 hours, were treated intravenously (i.v.) with PrLP doses of 0.05, 0.5, 5 and 50 mg/kg. After 30 min the animals received 0.2 ml of absolute ethanol per oral (p.o.). After 60 min of ethanol administration, the animals were sacrificed, their stomachs removed and analyzed to determine lesion index. To investigate the involvement of mediators in PrLP effect, animals received indomethacin (10 mg/kg, p.o.), L-NAME (20 mg/kg, i.p.), ODQ (10 mg/kg, i.p.), glibenclamide (5 mg/kg, i.p.) and capsazepine (5 mg/kg, i.p.) prior to treatment with PrLP (0.5 mg/kg i.v.). Misoprostol (50 µg/kg; p.o.), L-arginine (600 mg/kg; i.p.), diazoxide (3 mg/kg; i.p.) and capsaicin (0.3 mg/kg; p.o.) were used as standard-drug. To evaluate the effect of PrLP on the levels of NO3-/NO2, the dosage was performed in the homogenate of the stomach, but to investigate a possible antioxidant effect, it was carried out the measurement of the GSH levels in normal and injured stomachs. For sub-chronic toxicity animals were treated for 7 days with 50 mg/kg i.v., followed by evaluation of various parameters, such as: body weight, complete blood count, biochemical (urea, ALT, AST) and wet weight of vital organs (heart, spleen, liver and kidney). PrLP at doses of 0.5, 5 and 50 mg/kg was able to inhibit the gastric lesions by 81.9, 72.8 and 68%, respectively, retrieving the GSH levels in the mucosa by 105% compared with the ethanol group and PrLP did not alter the GSH levels in animals that were not ethanol-lesioned stomachs. Additionally, PrLP also increased in 26% NO3-/NO2- levels that were reduced by ethanol administration. Indometacin, L-NAME, ODQ, glibenclamide and capsazepine were able to reverse the PrLP protective effect, demonstrating the involvement of prostaglandins, NO, GMPc, potassium channels ATP-dependent and TRPV1 receptors in its mechanism of action. Furthermore, the treatment for 7 days with PrLP did not change any parameter evaluated showing safety in their use. These results indicate that PrLP have gastroprotective pharmacology activity on the gastric mucosa which seems to be mediated in part by modulation of prostaglandin, NO/cGMP/KATP pathway and TRPV1 receptors, which play a fundamental role in maintaining blood flow and gastric mucosa defense. PrLP acts avoiding depletion of GSH levels ethanol-induced. Since this is important for the maintenance of mucosal antioxidant defenses. Moreover, PrLP did not shown acute toxicity in animals.